Self-Efficacy sebagai mediator pengaruh stres kerja dan tipe kepribadian terhadap somatisasi pada anggota polisi satuan lalu lintas polda metro jaya - Isnidiniyah Pratiwi; Risatianti Kolopaking; Jahja Umar; Zulfa Indira (‎‎‎TAZKIYA Journal of Psychology, 2014)
This study aimed to examine the effect of emotional intelligence and attachment styles to the career decision making on SMAN 36 Jakarta. This study used a quantitative approach with multiple regression analysis. The sample totaled 237 high school students were taken using a non probability sampling technique. In this study, researcher modified the instrumental data, namely Assessment of Career Decision Making (ACDM), Wong And Law Intelligence Scale (WLEIS) and Adult Attachment Scale (AAS). Research data analysis using SPSS software, while for the construct validity testing using CFA. Based on the analysis of data, there is three research conclusions. The first conclusion is that there is a significant relationship between emotional intelligence and attachment styles to rational career decision making on students. It was found that the variable that have a significant effect is the use of emotions. The second conclusion is there is no significant relationship between emotional intelligence and attachment styles to the intuitive career decision making on students. It was found that the variable that have a significant effect is the avoidance attachment style. The final conclusion there is a significant relationship between emotional intelligence and attachment styles to dependent career decision making on students. It was found that the variable that have a significant effect is self emotions appraisal and regulation of emotions. For further study, the researcher suggested using other variables such as personality, social support, self efficacy and demographic variables.